Mitochondrial Genome Sequences of the Emerging Fungal Pathogen Candida auris - Misas, Elizabeth; Chow, Nancy A.; Gómez, Oscar M.; Muñoz, José F.; McEwen, Juan G.; Litvintseva, Anastasia P.; Clay, Oliver K. (Frontiers in Microbiology, 2020)
Candida auris is an emerging fungal pathogen capable of causing invasive infections in humans. Since its first appearance around 1996, it has been isolated in countries spanning 5 continents. C. auris is a yeast that has the potential to cause outbreaks in hospitals, can survive in adverse conditions, including dry surfaces and high temperatures, and has been frequently misidentified by traditional methods. Furthermore, strains have been identified that are resistant to two and even all three of the main classes of antifungals currently in use. Several nuclear genome assemblies of C. auris have been published representing different clades and continents, yet until recently, the mitochondrial genomes (mtDNA chromosomes) of this species and the closely related species of C. haemulonii, C. duobushaemulonii and C. pseudohaemulonii had not been analyzed in depth. We used reads from PacBio and Illumina sequencing to obtain a de novo reference assembly of the mitochondrial genome of the C. auris clade I isolate B8441 from Pakistan. This assembly has a total size of 28.2 kb and contains 13 core protein-coding genes, 25 tRNAs and the 12S and 16S ribosomal subunits. We then performed a comparative analysis by aligning Illumina reads of 129 other isolates from South Asia, Japan, South Africa and South America with the B8441 reference. The clades of the phylogenetic tree we obtained from the aligned mtDNA sequences were consistent with those derived from the nuclear genome. The mitochondrial genome revealed a generally low genetic variation within clades, although the South Asian clade displayed two sub-branches including strains from both Pakistan and India. In particular, the 86 isolates from Colombia and Venezuela had mtDNA sequences that were all identical at the base level, i.e., a single conserved haplotype or mitochondrial background that exhibited characteristic differences from the Pakistan reference isolate B8441, such as a unique 25-nt insert that may affect function.